Acute Oral and Dermal Toxicity of Mikania micrantha Essential Oil in Rats - Magpale, Jessa Mae; Dargantes, Kassey Alsylle; Dargantes, Alan; Dargantes, Sylvia; Daguro, Ted Aries; Vecino, Hannah Lois; Risma, Airish Jane; Enot, Melania (Universitas Airlangga, 2026)
The safety profile of Mikania micrantha essential oil has not been sufficiently characterized, despite its demonstrated bioactivity. To address this, the study evaluated its acute oral and dermal toxicity in Sprague-Dawley rats weighing 190–210g. Experimental groups included a negative control (distilled water), a positive control (DMSO+PBS), and three treatment groups (300, 1000, and 2000 mg/kg doses). The evaluation was conducted in accordance with OECD guidelines Nos. 423 and 402, pertaining to acute oral toxicity and acute dermal toxicity testing in animals, respectively. These protocols are standardized, providing internationally accepted procedures for assessing potential toxic effects of substances through oral and dermal routes. No mortalities or significant clinical abnormalities were observed over the 14-day observation period, while hemato-biochemical profiles remained within normal ranges. The parasitic cyst found in histopathology, containing larval cestodes, was an incidental finding and was not attributed to M. micrantha essential oil exposure. All these findings suggest that M. micrantha essential oil is well-tolerated by rats following acute oral and dermal administration, supporting its potential safe use in preclinical studies and laying the groundwork for its future development as a therapeutic agent in broader veterinary applications.